Isolation and Characterization of Human Platelet β-Thromboglobulin - Pepper, D. S.; Moore, S.; Cash, J. D. (Thrombosis and Haemostasis, 1975)
The thrombin released products from washed human platelets were separated by filtration on 4% agarose in 0.15 M NaCl. The high molecular weight PF4 complex was dissociated and re-chromatographed in 0.75 M NaCl. The low molecular weight fraction, including β thromboglobulin and a low MW anti-heparin was freed of plasminogen anti-activator by dissociation and chromatography in pH 3.5 pyridine acetic acid. The anti-activator was irreversibly denatured and albumin was removed in the void volume of the column. A more suitable purification procedure for recovery of all activities was affinity chromatography on heparin-agarose. The anti-activator was excluded and could be obtained free of plasma proteins by Sephadex G-200 chromatography. The βTG eluted at 0.3 M NaCl and the low MW anti-heparin at 1.5 M NaCl. The pure βTG (MW 36,000) was injected into rabbits and the resulting antiserum used to produce a radioimmunoassay for the release reaction in vivo.